2008
DOI: 10.1080/10253890701840610
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol concentrations, stress and quality of life in women with endometriosis and chronic pelvic pain

Abstract: The objective of this study was to evaluate the perceived stress index, quality of life, and hypothalamus-pituitary-adrenal axis activity in women with endometriosis and chronic pelvic pain. For the study, 93 women with endometriosis and 82 healthy women volunteered. The visual analogue scale (VAS) (0=no pain; 10=severe pain) was used to determine pain intensity; the perceived stress questionnaire (PSQ) defined stress index, and the health-related quality-of-life (HRQOL)-SF-36 questionnaire was used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(116 citation statements)
references
References 29 publications
8
101
0
7
Order By: Relevance
“…32 Consistent with this observation, higher serum cortisol levels are reported in infertile women with stage III to IV endometriosis than in healthy women, 33 although another study reported lower salivary cortisol levels in women with endometriosis when compared to controls, even though those women with endometriosis reported a high level of perceived stress. 34 The CORT is a glucocorticoid secreted by the cortex of the adrenal gland in response to the stimulation by adrenocorticotropic hormone. In rodents, CORT is a major indicator of stress.…”
Section: Discussionmentioning
confidence: 99%
“…32 Consistent with this observation, higher serum cortisol levels are reported in infertile women with stage III to IV endometriosis than in healthy women, 33 although another study reported lower salivary cortisol levels in women with endometriosis when compared to controls, even though those women with endometriosis reported a high level of perceived stress. 34 The CORT is a glucocorticoid secreted by the cortex of the adrenal gland in response to the stimulation by adrenocorticotropic hormone. In rodents, CORT is a major indicator of stress.…”
Section: Discussionmentioning
confidence: 99%
“…A presente revisão incluiu 12 publicações sobre qualidade de vida (QV) em pacientes com endometriose (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) , sendo um terço delas conduzido no Brasil (8,10,12,15) . A avaliação da QV envolve aspectos multidimensionais, uma vez que ela não é caracterizada pela ausência de doença, e sim pelo bem-estar biopsicossocial, pelo como as pessoas vivem, sentem e compreendem seu cotidiano.…”
Section: Resultsunclassified
“…A infertilidade pode até mesmo comprometer o relacionamento do casal, ocasionando uma desestabilização no contexto familiar e social do indivíduo, com presença de sentimento de fracasso e inferioridade, isolamento e redução da autoestima, com consequentes alterações psicológicas, como ansiedade, depressão e estresse (Monga, Alexandrescu, Katz, Stein, & Ganiats, 2004;Barbosa & Rocha-Coutinho, 2007). Esse último foi alvo de investigação em dois estudos que mostraram ní-veis elevados de estresse em pacientes com endometriose (Petrelluzzi, Garcia, Petta, Grassi-Kassisse, & Spadari-Bratfisch, 2008;Siedentopf et al, 2008). Ainda, em relação à ansiedade e à depressão na infertilidade, Golombok (1992) aponta que a primeira pode ser decorrente dos longos processos de tratamento e do temor de que eles fracassem, e a segunda está relacionada com a inabilidade para conceber.…”
Section: Discussionunclassified